SOCIAL SERVICES AS A SOCIAL INVESTMENT ON THE EXAMPLE OF A NEW INSTITUUTION OF SOCIAL CENTERS IN POLAND, FROM THE PERSPECTIVE OF THE SOCIAL WORKERS - Grewiński, Mirosław; Kawa, Marek (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The aim of the article is to present the empirical research conducted among Polish social workers in November of 2020 on the newly created institution named in Polish - - Centrum Usług Społecznych, CUS (Social Service Centers). The article also presents the theoretical framework, but mostly the authors focus on presenting empirical research of 79 social welfare centers in Poland. The main research problem proposed within the article was how social workers perceive the creation of a new institution in municipalities - social service centers and what deficits and strengths they see in the field of creating new social services, that meet new challenges such as aging of society, transformations of labor markets and changes within the family, ecological threats and new pandemics.